2, 2′‐Bipyridine Equipped with a Disulfide/Dithiol Switch for Coupled Two‐Electron and Two‐Proton Transfer. Issue 19 (6th March 2018) - Cattaneo, Mauricio; Schiewer, Christine E.; Schober, Anne; Dechert, Sebastian; Siewert, Inke; Meyer, Franc
Abstract: [1, 2]Dithiino[4, 3‐b:5, 6‐b′]dipyridine (1 ) and its protonated open form 3, 3′‐dithiol‐2, 2′‐bipyridine (2 ) were synthesised and their interconversion investigated. The X‐ray structure of2 revealed an anti orientation of the two pyridine units and a zwitterionic form. In depth electrochemical studies in combination with DFT calculations lead to a comprehensive picture of the redox chemistry of1 in the absence and presence of protons. Initial one‐electron reduction at E 1 =−1.20 V results in the formation of the radical anion1 red with much elongated S−S bond, which readily undergoes further reduction at E 2 =−1.38 V. Water triggers a potential inversion ( E ≥−1.13 V for the second reduction) as the radical anion1 red is protonated at its basic N atom. DFT studies revealed that S−S bond breaking and twisting of the pyridine units generally occurs after the second reduction step, whereas the potential inversion induced by protonation is a result of charge compensation. The CV data were simulated to derive rate constants for the individual chemical and electrochemical reactions for both scenarios in the absence and presence of protons. Abstract : Couples and switches : Electrochemical investigation of a new dithiine that amalgamates the 2 e − /2 H + disulfide/dithiol couple with the 2, 2′‐bipyridine scaffold shows that protonation by a weak acid such as water facilitates the second reduction and triggers potential inversion while inducing a switch from an EEC mechanism to an ECEC mechanism.